The Influence of Social Media and Brand Awareness on Interest to Buy Wardah Cosmetic Products Mediated by Trust - Sutrisno, Sutrisno; Parso, Parso (ProBisnis : Jurnal Manajemen, 2023)
This quantitative research is to test the influence of social media, brand awareness and trust on buying interest in Wardah cosmetics, where trust is a mediating variable. Analysis using the Structural Equation model method with SmartPLS 3.0 software. In this research, the population is Wardah Cosmetics consumers in Jakarta who actively use Instagram social media, therefore the population is unknown, so based on the calculation the sample size for this research is 100 respondents. This research uses a non-probability sampling strategy with a purposive sampling method. The results of this study show that the influence of social media is not significant, while brand awareness and trust have a significant impact. The influence of social media on purchasing interest is limited due to various factors, such as differences in social media use between different generations, information overload on social media, and consumer preferences for direct shopping experiences. On the other hand, brand awareness has a significant impact because it makes it easier for consumers to recognize Wardah products among the various existing choices. Brand awareness is also closely related to perceived product quality, personal experience, promotions, and brand reputation, all of which contribute to increasing interest in purchasing Wardah cosmetic products. Trust also plays an important role in shaping purchasing interest, because it provides a psychological and social basis for consumer decision making.